The Lifestyle and Halal Industry Methods with Local Culture: Study of Tourism and Halal Products in Nusa Tenggara Timur 2020 - Ahmad Bahiej; Makhrus Munajat; Diky Faqih Maulana (IAIN Manado, 2021)
The development of the tourism industry based on sharia principles has begun to attract the attention of Muslim tourists in various regions, so it needs to manage seriously and professionally. For example, in Labuan Bajo, Nusa Tenggara Timur is designated one of the four priority tourist destinations. So it is necessary to pay attention to the phenomenon that continues to develop at this time both at the local and global level, which makes halal tourism destinations a new alternative for the Muslim community to travel. This research is qualitative research with field studies and uses a legal and juridical sociology approach. By referring to several methods for conducting ijtihad, both individually and collectively, as is done by DSN-MUI with the concept of maslahah mursalah, istihsan or 'urf. The results of the study state that halal tourism is a development that cannot deny. This new concept has a benchmark as stated by the DSN-MUI with the principle of the United Nations provisions. Tourists in halal tourism not limited by differences in ethnicity, religion, race, and between groups. If there are restrictions, it is counterproductive or contrary to the essential nature of Islamic teachings that oriented to rahmatan lil 'alamin. So the halal tourism industry is an expression of the teachings of rahmatan lil 'alamin and a vehicle for friendship between people who are different in various aspects. It hope that halal tourism can develop to meet the needs of Muslim tourists so that they do not only visit conventional tourism, thus creating benefits.